Adolescent Sleep Disturbance, Emotion Regulation and Borderline Features in an Inpatient Setting. Issue 6 (2nd November 2022) - Wall, Kiana; Vanwoerden, Salome; Penner, Francesca; Patriquin, Michelle; Alfano, Candice A.; Sharp, Carla
ABSTRACT: Objective : The current study aimed to examine the relation between sleep disturbance, emotion dysregulation and borderline personality features in adolescent inpatients. Method : N = 217 adolescents (67.1% female; ages 12–17) with the following racial/ethnic breakdown: 67.4% White, 3.7% Hispanic, 2.8% Asian, 1.8% African American, and 6.4% multiracial) completed self-report measures of sleep disturbance, emotion dysregulation and borderline personality symptoms at admission to, discharge from, and at 6-months-post discharge from an inpatient psychiatric hospital. Group comparison and path analyses were conducted to examine differences in sleep disturbance between those with and without borderline personality disorder and the mediating role of emotion dysregulation in the relation between sleep disturbance and borderline personality features. Results : Borderline personality features and emotion dysregulation were significantly related to indices of sleep disturbance. Path models revealed that some sleep disturbance indices at admission directly predicted levels of borderline features at discharge and at 6-months-post-discharge. However, none of the indirect pathways between sleep disturbance at admission, emotion dysregulation at discharge, and borderline features at discharge or 6-months post-discharge were significant. Conclusions : Findings are consistent with prior literature which suggest that a unique relation exists between sleep disturbance and BPD, beyond comorbid depression symptoms. However, contrary to our hypotheses, the current study did not provide empirical support for the mediating role of emotion regulation in this relation. These findings have implications for existing personality disorder and sleep interventions and suggest further research into the mechanisms underlying the relation between sleep disturbance and borderline personality pathology is necessary.